PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Anita Eviana, 09.05.52.0108; Nurhayati, Ida (Students Journal of Accounting and Banking, 2013)
This research is a study that tested the effect of investment decisions, financing decisions, and dividend policy on firm value. Functions of financial management is to plan, locate and use the funds to maximize the firm value. In a firm will take policies related to funding for business growth and obtain optimal results. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) in the year 2008-2011. The sample used in this study researchers used purposive sampling criteria manufacturing companies that have positive earnings and cash dividend as well as manufacturing companies that issue financial statements in rupiah and obtain a sample of 173 sample firms. Corporate data and then tested with the classical assumption of normality, multikolonieritas, heteroscedasticity, and autocorrelation. Further analysis researchers used multiple regression analysis to explain the relationship between variables. Based on the results of this study concluded: The results indicate that the variable dividend policy and investment decisions have positive and significant effect on firm value, while funding decisions and significant negative effect on firm value. Keywords: Investment Decisions, Financing Decisions, Dividend Policy, and Firm Valuesââ.